Numerical simulation of condensation for R410A at varying saturation temperatures in mini/micro tubes. (3rd March 2016) - Zhang, Jingzhi; Li, Wei; Minkowycz, W. J.
ABSTRACT: Heat transfer and pressure drop characteristics of condensation for R410A inside horizontal tubes (dh = 0.25, 1, and 2 mm) at saturation temperatures Tsat = 310, 320, and 330 K are investigated numerically. The results indicate that local heat transfer coefficients and pressure drop gradients increase with increasing mass flux and vapor quality and with decreasing tube diameter and saturation temperature. Liquid film thickness also increases with increasing saturation temperature because of the lower surface tension at higher saturation temperature. When gravity dominates the condensation process, a vortex with its core lying at the bottom of the tube is found in the vapor phase region. For the annular flow regime, stream traces point from the symmetry plan to the liquid–vapor interface, where the vapor phase becomes the liquid phase. Numerical heat transfer coefficients and pressure drop gradients are compared to available empirical correlations. Two new models for heat transfer coefficients and frictional pressure drop gradients are developed based on the numerical work.